The Effect of Jacobson’s Relaxation Therapy on Shortness of Breath in Patients with Bronchitis Chronic - Herawati, Isnaini; Hapsari, Dela Oktavia (Universitas Muhammadiyah Surakarta, 2017)
Lower respiratory tract infections are a serious public health problem in Indonesia. In 2007, the number of people infected with bronchitis is about 1.6 million people and the prevalence has not changed significantly since then. Several therapeutic techniques have been developed to resolve the problems related to chronic bronchitis, including relaxation therapy to decrease shortness of breath. This study was conducted on 13 patients with chronic bronchitis who were given Jacobson’s Relaxation Therapy for 25—30 minutes with frequency three times a week and performed for four weeks. The degree of shortness of breath was measured using Borg Scale before and after the treatment of Jacobson’s relaxation therapy. In average, subjects endured shortness of breath with a degree of 2.69 before treatment, and decreased to 0.77 after the treatment. Wilcoxon signed-rank test obtained p value = 0.001, which means the effect of Jacobson’s relaxation therapy on the degree of shortness of breath.